Chapter 3 Rethinking the framing of climate change adaptation Knowledge, power, and politics - Morchain, Daniel (Taylor & Francis, 2018)
Adaptation to climate change has always been part of life on earth. Yet, according to the scientific literature - such as the Fifth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) - the increased magnitude of global warming the planet is currently experiencing further exacerbates the negative impacts of climate change on people - increasing risk and reducing their capacity to adapt. This is particularly the case for marginalised people in the Global South living in poverty (IPCC 2014). Wide recognition that industrialised countries are overwhelmingly responsible for these changes has, albeit slowly, led to governments of industrialised countries increasingly financing climate change adaptation initiatives in the Global South.